'Fifty-two doors': identifying cultural significance through narrative and nostalgia in Lakhnu village - Stephens, John (Taylor Francis, 2014)
This paper proposes an alternative way of evaluating heritage values in the assessment of an abandoned school building in Lakhnu, a small rural Indian village in the state of Uttar Pradesh. Its aim is to re-think the appropriateness of professionally assessed methodologies, such as the Australian ICOMOS Burra Charter, and find others which are more inclusive and sensitive of community views and aspirations. Villagers claim this building as a key part to their cultural heritage, and view its desertion and disintegration with frustration. As part of a larger scheme to improve village infrastructure and to enable its empowerment, the aim is to assess the significance of this place to the villagers, facilitate its conservation and investigate possible outcomes for its use through community participation. In this context, the concept of narrative is offered as means to establish the community meaning of a place. Narratives are powerful ways in which people understand their environment and structure a view of the world. Using stories told by villagers about their relationship with the building, this paper argues that narrative can offer an alternative method of understanding heritage significance.